A new physical insight of RESURF effects based on gradual charge appointment concept for bulk silicon lateral power devices. (April 2016) - Zhang, Jun; Guo, Yu-Feng; Sun, Yabin; Yang, Kemeng; Lin, Hong; Xia, Xiaojuan; Zhang, Changchun
Abstract: A novel gradual charge appointment concept is proposed to provide a clear physical insight of RESURF effects in bulk silicon lateral power devices. Due to the expandable substrate depletion region in silicon power device, the Linearly Graded Approximation is unable to fully describe the 2-D coupling effects between vertical and lateral junction. In this paper, by defining a charge appointment line, the lateral abrupt junction behaves as an effective gradual junction, thus resulting in the wider depletion layer, lower field peak and higher breakdown voltage. Based on the hypothesis, a simple 1-D model is proposed to quantify the breakdown voltage of the bulk silicon RESURF device and formulize the surface electric field. To our knowledge, the proposed model is the first 1-D model for bulk silicon RESURF device which can accurately describe the surface field profiles under various applied voltages and structure parameters. Furthermore, we provide a new RESURF criterion to explore the sensitivity of the breakdown voltage to structure parameters. Fair agreements among the analytical, numerical and experimental results verify the availability of the proposed concept and model. Highlights: A novel gradual charge appointment concept is proposed for exploring the RESURF effect in bulk silicon lateral power device. The first proposed 1-D model for bulk silicon power device which can accurately describe the surface electric field profiles. The gradual charge appointment provides a novel explanation for the lateral electric field reshaping/reduction effects. A novel RESURF criterion is proposed for optimizing the geometric parameters of RESURF lateral power devices.